Web Dynamics Adapting to Change in Content, Size, Topology and Use - Levene, Mark; Poulovassilis, Alexandra (Springer Berlin Heidelberg, 2004)
The World Wide Web has become a ubiquitous global tool, used for finding infor mation, communicating ideas, carrying out distributed computation and conducting business, learning and science. The Web is highly dynamic in both the content and quantity of the information that it encompasses. In order to fully exploit its enormous potential as a global repository of information, we need to understand how its size, topology and content are evolv ing. This then allows the development of new techniques for locating and retrieving information that are better able to adapt and scale to its change and growth. The Web's users are highly diverse and can access the Web from a variety of devices and interfaces, at different places and times, and for varying purposes. We thus also need techniques for personalising the presentation and content of Web based information depending on how it is being accessed and on the specific user's requirements. As well as being accessed by human users, the Web is also accessed by appli cations. New applications in areas such as e-business, sensor networks, and mobile and ubiquitous computing need to be able to detect and react quickly to events and changes in Web-based information. Traditional approaches using query-based 'pull' of information to find out if events or changes of interest have occurred may not be able to scale to the quantity and frequency of events and changes being generated, and new 'push' -based techniques are needed
Keywords: Information Systems Applications (incl. Internet); Database Management; Information Storage and Retrieval; User Interfaces and Human Computer Interaction; e-Commerce/e-business; Application software; Database management; Information storage and retrieval; User interfaces (Computer systems); E-commerce; World Wide Web; Leistungsbewertung; Aufsatzsammlung